EVALUATION OF PHYSICAL AND FUNCTIONAL CAPACITY OF OBESE PEOPLE THROUGH 6MWT (Fiep Bulletin - online, 2016)
Introduction: Obesity is now a major public health problems, the high weight associated with inactivity, is directly related to pathological conditions that cause high morbidity and mortality. Compared to the existing malnutrition in poor countries, obesity is still considered more serious because its pathological effects in the body lead from premature death to limitations that impair directly the quality of life of these people. Objective: To evaluate the physical and functional capacity of obese patients undergoing bariatric surgery. Methods: Analysis of patients' medical records that are monitored and evaluated at the Clinic HUOP- Cascavel / PR who underwent functional test (6MWT) and answered the questionnaire of quality of life (HAQ-20). Results: We evaluated medical records of 21 patients, 18 women and 3 men, aged 23 and 58, the mean BMI obtained was 41.3. The mean of 6'WT was 451,5m and the average percentage obtained was 93.2%. Conclusions: The 6MWT proved to be an appropriate test for the obese population. The sample showed no functional capacity physically changed, which reduces the risks of surgical intervention.
Keywords: Physical aptitude; Obesity; Quality of life.